2022
DOI: 10.1002/adhm.202202652
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Responsive Nanocomposites for Synergistic Antibacterial Therapies Facilitating Bacteria‐Infected Wound Healing

Abstract: The rising dangers of bacterial infections have created an urgent need for the development of a new generation of antibacterial technologies and therapeutics. Antibacterial photodynamic therapy (PDT), considered as a noninvasive treatment with no drug resistance, has become a new promising photochemistry‐involved treatment strategy. Titanium oxide (TiO2) is proved to be a very efficient PDT agent among the photosensitive materials, while the property of a large bandgap of TiO2 makes it only be excited by ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…Its superior mechanical properties and low cost make it ideal material for implant and antibacterial fillers. Titanium dioxide has a wide antibacterial spectrum and has antibacterial effect on S. mutans , S. aureus , Fusobacterium nucleatum ( F. nucleatum ), P. gingivalis , etc [ 61 ]. Totu et al.…”
Section: Nano-antibacterial Materialsmentioning
confidence: 99%
“…Its superior mechanical properties and low cost make it ideal material for implant and antibacterial fillers. Titanium dioxide has a wide antibacterial spectrum and has antibacterial effect on S. mutans , S. aureus , Fusobacterium nucleatum ( F. nucleatum ), P. gingivalis , etc [ 61 ]. Totu et al.…”
Section: Nano-antibacterial Materialsmentioning
confidence: 99%
“…Similarly, Cheng et al synthesized the TiO 2 and polydopamine cross-linked mesoporous nanoparticles (mTiO 2 @PDA NPs), which shows a combined synergistic effect of sonodynamic therapy and photothermal therapy under the dual excitation of NIR and ultrasound. [288] In addition, Cheng et al reported on the light-responsive photothermal and ROS synergistic therapy of ZnTCPP(porphyrin-metal complex)/Ti 3 C 2 T x organic-inorganic composites. [289] The Schottky junction formed between Ti 3 C 2 T x and ZnTCPP promotes visible light utilization, accelerates charge separation, and enhances the mobility of photogenerated charges.…”
Section: Photoelectric Conversion Biomaterialsmentioning
confidence: 99%
“…synthesized the TiO 2 and polydopamine cross‐linked mesoporous nanoparticles (mTiO 2 @PDA NPs), which shows a combined synergistic effect of sonodynamic therapy and photothermal therapy under the dual excitation of NIR and ultrasound. [ 288 ] In addition, Cheng et al. reported on the light‐responsive photothermal and ROS synergistic therapy of ZnTCPP(porphyrin–metal complex)/Ti 3 C 2 T x organic–inorganic composites.…”
Section: Multifunctional Materials For Electronic Applicationsmentioning
confidence: 99%
“…[4][5][6] However, while antibiotics can achieve rapid sterilization, the indiscriminate use and abuse of antibiotics can cause strong side effects in the human body and accelerate the emergence of drug-resistant bacteria, as well as super drug-resistant bacteria. [7,8] To solve this tricky dilemma, various nanomaterials, such as precious metals, [9] semiconductors, [10] and carbon-based materials, [11] have proliferated in the field of antimicrobial research. As they can kill bacteria by generating reactive oxygen species (ROS, such as 1 O 2 , •OH, and •O 2 − ) through local plasma effects, the release of ions, or photogenerated electrons and holes react with surrounding oxygen or water, these antibacterial nanomaterials came to be known as photodynamic therapy (PDT) in killing bacteria by damaging their DNA, enzymes, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this tricky dilemma, various nanomaterials, such as precious metals, [ 9 ] semiconductors, [ 10 ] and carbon‐based materials, [ 11 ] have proliferated in the field of antimicrobial research. As they can kill bacteria by generating reactive oxygen species (ROS, such as 1 O 2 , · OH, and · O 2 − ) through local plasma effects, the release of ions, or photogenerated electrons and holes react with surrounding oxygen or water, these antibacterial nanomaterials came to be known as photodynamic therapy (PDT) in killing bacteria by damaging their DNA, enzymes, and proteins.…”
Section: Introductionmentioning
confidence: 99%